2020
DOI: 10.1088/1757-899x/768/2/022008
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Parameter Optimization of Self-piercing Riveted Joint for Aluminum Alloy Plate

Abstract: Self-piercing riveting is a connection technology to achieve efficient connection of aluminum alloy plates, and the quality of the connection mainly depends on the rivet and mold parameters. This paper establishes a self-piercing riveting simulation analysis model based on the ALE method, and verifies the accuracy of the model by comparing the simulation and experimental results. Five parameters such as rivet length and mould radius are selected, and the undercut amount, bottom thickness, remaining thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…To impede simulation termination because of large element distortion, arbitrary Lagrangian-Eulerian (ALE) mapping was used to the sheet materials as a re-meshing technique. Zhong et al 22) reported that the ALE coordinate system could effectively interpret the trends in the process of material deformation and reduce mesh distortion during the large plastic deformation of the SPR process. The mechanical and elastoplastic properties of work pieces were employed to obtain an appropriate calculation of their deformation during the riveting process.…”
Section: Finite Element Analysis Of Spr Jointsmentioning
confidence: 99%
“…To impede simulation termination because of large element distortion, arbitrary Lagrangian-Eulerian (ALE) mapping was used to the sheet materials as a re-meshing technique. Zhong et al 22) reported that the ALE coordinate system could effectively interpret the trends in the process of material deformation and reduce mesh distortion during the large plastic deformation of the SPR process. The mechanical and elastoplastic properties of work pieces were employed to obtain an appropriate calculation of their deformation during the riveting process.…”
Section: Finite Element Analysis Of Spr Jointsmentioning
confidence: 99%